PENGARUH DEBT TO EQUITY RATIO, NET PROFIT MARGIN DAN CURRENT RATIO TERHADAP HARGA SAHAM PADA PT. ASTRA INTERNATIONAL TBK PERIODE 2013-2022 - Amri, Saipul; Sutiman (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of Debt to Equity Ratio (DER), Net Profit Margin (NPM) and Current Ratio (CR) on Share Price at PT Astra International Tbk for the period 2013-2022. This type of research is descriptive quantitative with the analysis method used is descriptive statistics, classical assumption test, hypothesis testing (t test and F test) with a significant level of 0.05 (5%) and the data source used is secondary data. From the results of this study indicate that Debt to Equity Ratio (DER) has no effect on Stock Price, this is evidenced by (t test) that the tcount value (-1.908) < t table (2.447) and a significant value of (0.105) > (0.05). The results of this study indicate that Net Profit Margin (NPM) has no effect on Stock Price, this is evidenced by (t test) that the tcount value (-0.925) < t table (2.447) and a significant value (0.391) > (0.05). The results showed that Current Ratio (CR) has a negative effect on Stock Price, this is evidenced by (t test) that the tcount value (-4.130) > t table (2.447) and a significant value (0.006) < (0.05). Simultaneous testing shows that Debt to Equity Ratio (DER), Net Profit Margin (NPM) and Current Ratio (CR) simultaneously have a significant effect on Stock Price, this is evidenced by (f test) that the Fcount value is 9.771> Ftable 4.76 with a significant value of 0.010 <0.05.